Discovering Genesis : content, interpretation, reception - Provan, Iain W. (Iain William), 1957- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
Iain Provan here offers readers a compact, up-to-date, and student-friendly introduction to the book of Genesis, focusing on its structure, content, theological concerns, key interpretive debates, and historical reception. Drawing on a range of methodological approaches (author-, text-, and reader-centered) as complementary rather than mutually exclusive ways of understanding, Discovering Genesis encourages students to dig deeply into the theological and historical questions raised by the text. It provides a critical assessment of key interpreters and interpretive debates, focusing especially on the reception history of the biblical text, a subject of growing interest to students and scholars of the Bible.
Introduction -- Strategies for reading 1 : before the Renaissance -- Strategies for reading 2 : from the Renaissance until the present -- The world of Genesis : locating the text in its time and place -- Creation : Genesis 1.1-2.25 -- The entrance of evil : Genesis 3.1-24 -- From Cain to the Great Flood : Genesis 4.1-6.8 -- From Noah to the Tower of Babel : Genesis 6.9-11.26 -- Abraham, Sarah and Isaac : Genesis 11.27-25.18 -- The Jacob story : Genesis 25.19-37.1 -- The Joseph story : Genesis 37.2-50.26.
Includes bibliographical references (pages 190-198) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. Genesis - Criticism, Interpretation, Etc; Criticism, interpretation, etc